Chapter 6 Reconfiguring the Viewer Modes of Perception and Attention in Immersive Museum Experience - Bertrand, Stéphanie (Taylor & Francis, 2024)
Cultural organizations are increasingly turning to immersive technologies such as Extended Reality to create more embodied and interactive experiences of remote cultural objects. Yet, museum computing's overriding focus on cultural understandings of presence in terms of objects has obscured the broader role that these systems' reconfiguration of perception and attention play in shaping user experience. While cultural presence generally complicates the issue of technological mediation, the chapter argues that modern and contemporary visual art actually provides a unique test case to disentangle the nexus of immersion, presence, attention and ability at the core of these experiences. Its central claim is that the way in which wearable technologies 'augment' users by sensing, capturing, analyzing and processing sensorimotor action should be taken into account in the curation and design of future immersive experiences rather than assuming that the technology will eventually become transparent and 'naturalized.'